The interaction of smoking habit, SLPI and AnxA2 in HPV associated head and neck and other cancers. (2021) - Hoffmann, Markus; Quabius, Elgar Susanne; Fabian, Alexander; Laudien, Martin; Ambrosch, Petra
Highlights: Smoking is associated with an increased SLPI and AnxA2 expression in human mucosa with surplus of SLPI. SLPI and HPV interact with AnxA2 with this interaction being pivotal for cell entry of HPV. HPV-positive carcinomas are associated with non-smoking and low SLPI levels and HPV-negative carcinomas are associated with smoking and high SLPI levels. The interaction between smoking, SLPI and AnxA2 expression may explain the interaction between smoking and HPV. Abstract: Six own studies confirm a correlation between smoking, expression of the secretory leukocyte protease inhibitor (SLPI, an antileukoproteinase) and expression of Annexin A2 (AnxA2), and their influence on human papilloma virus (HPV)-infections. SLPI and HPV are ligands of AnxA2. This correlation was tested on 928 tissue samples from 892 patients in six independent studies [squamous cell carcinoma of the head and neck (HNSCC), n  = 522; non-neoplastic tonsils n  = 214; clinically normal mucosa, n  = 93 (of these n  = 57 were obtained from patients treated for non-malignant diseases and n  = 36 were obtained from HNSCC-patients) and vulvar squamous cell carcinoma (VSCC) n  = 99]. HPV-DNA-status was determined by GP5+/GP6+-PCR, followed in case of HPV-positivity by Sanger sequencing and RT-PCR using HPV-type specific primers. SLPI- and AnxA2-gene-expression was determined by RT-q-PCR; SLPI-protein-expression was additionally determined by immunohistochemistry (IHC); the data were correlated with each other and with patient characteristics. Smoking results in increased SLPI-gene- and protein- and AnxA2-gene-expression with significantly higher SLPI- than AnxA2-gene-expression. SLPI is decreased in non-smokers with a continuous AnxA2-surplus. HPV-status correlates with smoking habit, with smokers being mostly HPV-negative and non-smokers HPV-positive. We hypothesize that smoking leads to SLPI-overexpression with SLPI-binding to AnxA2. Thus, HPV cannot bind to AnxA2 but this seems pivotal for HPV-cell-entry. Smoking favors SLPI-expression resulting in HPV-negative carcinomas, while HPV-positive carcinomas are more common in non-smokers possibly due to a surplus of unbound AnxA2. In addition, the hypothesis may contribute to understand why smokers show increased oral HPV-prevalence in natural history studies but do not necessarily develop HPV-associated lesions.